2022
DOI: 10.1002/lary.30033
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Positive Surgical Margins in cT1‐T2 Oral Cavity Squamous Cell Carcinoma

Abstract: Objectives/Hypothesis To evaluate trends in contemporary positive surgical margin incidence in cT1‐T2 oral cavity squamous cell carcinoma and to evaluate factors associated with surgical margin status. Study Design Retrospective analysis of large dataset. Methods Retrospective analysis of the National Cancer Database. Results Between 2004 and 2016, 39,818 patients with cT1 or cT2 oral cavity squamous cell carcinoma received primary curative‐intent surgery. Positive surgical margins were present in 7.95% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Robinson et al, who performed a NCDB analysis of patients with cT1-T2 disease, found the overall positive margin rate to be 7.9%. 5 They found the annual positive margin rate for early-stage disease to be decreasing from 2004 to 2016. These investigators attributed this, in part, to the fact that more patients were receiving treatment at academic centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robinson et al, who performed a NCDB analysis of patients with cT1-T2 disease, found the overall positive margin rate to be 7.9%. 5 They found the annual positive margin rate for early-stage disease to be decreasing from 2004 to 2016. These investigators attributed this, in part, to the fact that more patients were receiving treatment at academic centers.…”
Section: Discussionmentioning
confidence: 99%
“…these factors to be similarly associated with positive margins in cT1-T2 disease. 5,6 In addition, the odds of a positive surgical margin were nearly 2 times greater for tumors with a hard palate primary compared to those of the oral tongue. A similar increase in odds of positive margin for hard palate tumors was appreciated in cT1-T2 disease and was attributed to inability to perform frozen section analysis on bony portions of resection specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average travel distance was nearly twice as far for patients treated at academic facilities compared to nonacademic facilities (56 vs 28 miles, respectively). An average travel distance of over 50 miles has been used in prior studies to divide patients into “near” and “far” groups, 14 and may partially explain the higher rates of missed adjuvant therapy among patients treated at academic facilities. Although NCDB does report whether surgery and radiation were performed at the same site, there is no such data for patients who did not receive radiation, so it is unclear whether radiation treatment was available closer to home for patients who had surgery at academic centers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Royal College of Pathologists, histological tumor‐free margins of <1 mm are considered “involved”, 1–5 mm “close”, and >5 mm “clear” 6 . Involved margins are reported in 20%–41% of the BMSCC patients’ 7–10 . Most of these involved margins are located in the deep resection plane 11 .…”
Section: Introductionmentioning
confidence: 99%